Evaluation of unhealthy cervix by Pap smear and colposcopy guided biopsy - Venkatesh, Meenakshi; Gopalan, Ushadevi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Cancer of cervix ranks as the third common malignancy in females worldwide. In developing countries like India, carcinoma cervix is the second commonest malignancy affecting females. India accounts for 18% of the global burden of carcinoma cervix. To address the above problem a literature review was done using search engines like PubMed, Google scholar etc to evaluate the unhealthy cervix by comparison of Pap smear and colposcopy guided biopsy.